2016
DOI: 10.4085/1062-6050-51.3.05
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Reported Concussion Injury Rates and Time Loss From Participation: An Update of the National Collegiate Athletic Association Injury Surveillance Program From 2004–2005 Through 2008–2009

Abstract: Epidemiologic studies have identified differences in concussion incidence between the sexes. However, few authors to date have updated injury rates (IRs) and time loss between male and female concussed athletes.Context: To examine sex differences in IRs and time loss in concussed National Collegiate Athletic Association (NCAA) athletes.Objective: Descriptive epidemiologic study.Design: National Collegiate Athletic Association athletics.Setting: A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
143
4
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 223 publications
(159 citation statements)
references
References 20 publications
9
143
4
3
Order By: Relevance
“…Previous studies commonly report increased SRC incidence in female contact sports when compared to males, which was not supported by our present data. In addition, females typically fare worse than males after SRC . Both initial symptoms and duration of symptom are commonly worse, findings supported by our present study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Previous studies commonly report increased SRC incidence in female contact sports when compared to males, which was not supported by our present data. In addition, females typically fare worse than males after SRC . Both initial symptoms and duration of symptom are commonly worse, findings supported by our present study.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies commonly report increased SRC incidence in female contact sports when compared to males, 36 which was not supported by our present data. In addition, females typically fare worse than males after SRC.…”
contrasting
confidence: 99%
“…These results may reflect the fact that girls do not have enough strength and awareness to avoid collisions and are not physically able to withstand a collision. Female sex has been associated with a higher risk of sport-related concussions 3 9 11. Our study identifies a higher risk of concussion in men, but the result was not statistically significant.…”
Section: Discussioncontrasting
confidence: 69%
“…There was strong evidence of a relationship between acute or subacute symptom burden and worse clinical outcome, although a few studies have not found this association (box 3).
Preinjury characteristics associated with recovery Younger age: Yes: Chermann81; Field82; Terwilliger83; Covassin84; Majerske85; Pellman86; Zuckerman71 No: Lau87; Hang30; McDevitt88; Nelson21; Asplund89; Chrisman75; Vargas74; Morgan58; Meehan42; Meehan90; Meehan6; McCrea91; Lee70; Baker92; Greenhill93; Nelson78; Corwin48; Preiss-Farzanegan94; Heyer80; Kontos67; Kriz77; Miller56, Ellis95; Gibson96 Female sex: Yes: Baker31; Berz97; Henry29, Kostyun79; Bock49; Zuckerman98; Covassin84; Covassin73; Covassin53; Majerske85; Colvin99; Eisenberg68; Ellis95; Miller56; Preiss-Farzanegan(in adults)94; Heyer80; Zemek57 No: Chermann81; Moor100; Hang30; Nelson21; Mayers101; Asplund89; Black72; Chrisman75; Zuckerman102; Zuckerman103; Vargas74; Terwilliger83; Morgan58; Frommer52; Baker92; McDevitt88; Nelson78; Lax104; Ono105; Preiss-Farzanegan (in children/adolescents)94; Covassin106; Kontos67; Wasserman41; Yang107; Meehan90; Gibson96; Meehan6 Race (non-white): Yes: Vargas74; Kontos
…”
Section: Resultsmentioning
confidence: 99%